Mitochondrial complex assembly - Nijtmans, Leo (Henry Stewart Talks, 2007)
The mitochondrial oxidative phosphorylation system, Components: mitochondrial subunits, nuclear subunits and prosthetic groups, Coordination of assembly, Factors involved in assembly, Defects in OXPHOS assembly, Complex IV assembly, Complex I assembly, Complex I assembly defects, Chaperones for complex I, Supercomplexes of the OXPHOS system
Archived at 2018/10/28